Aberrant expression of multiple γ-glutamyltransferases is associated with tumor progression and patient outcome in prostate cancers - Jiang, Wencong; Liu, Wang; Zhao, Jiang; Xu, Zhijian; Xi, Ming; Wang, Xiangwei; Li, Benyi (Frontiers in Oncology, 2025)
IntroductionThe human gamma-glutamyltransferase (GGT) is a membrane-bound extracellular glycoprotein with an enzymatic activity that cleaves gamma-glutamyl peptide bonds in glutathione and other peptides and transfers the gamma-glutamyl moiety to acceptors. It has been shown aberrant expression of GGT proteins in human cancers while their expression profiles in prostate cancers are not reported.MethodsIn this study, we analyzed the expression profiles of all protein-coding GGT genes using the TCGA-PRAD RNA-seq dataset derived from primary prostate cancers. GGT family gene expression profiles were also analyzed using the SU2C/PCF RNAseq dataset derived from aggressive late-stage prostate cancer patients. Androgen modulation of GGT family gene expression was analyzed using multiple NCBI/GEO datasets.ResultsOur results showed that prostate tissues expressed four major isoforms of GGT family genes (GGT1/5/6/7), of which GGT1 expression was upregulated but GGT6/GGT7 expression was downregulated in cancer tissues compared to benign tissues. However, GGT5 expression was increased along with tumor stage progression and associated with worse progression-free survival. GGT6 expression exhibited a superb AUC value in prostate cancer diagnosis and was associated with favorable progression-free survival. GGT1 expression was highly increased but GGT6/GGT7 expression was largely reduced in ERG-fusion-positive cases. In CRPC tumors, GGT6 expression was suppressed in patients with anti-AR therapies, which was reversed when patients were taken off the treatment. This AR-dependent modulation was confirmed in LNCaP cells and LuCaP35 xenograft models. In addition, compared to CRPC-Adeno tumors, treatment-induced NEPC tumors showed a reduced GGT1 but an elevated GGT7 level, which was in line with higher levels of GGT7 in NEPC H660 cells.ConclusionOur data suggests that GGT6 is a new AR downstream target but GGT7 is a potential NEPC biomarker.